Coronary heart disease mortality among young adults in Scotland in relation to social inequalities: time trend study. (14th July 2009) - O'Flaherty, Martin; Bishop, Jennifer; Redpath, Adam; McLaughlin, Terry; Murphy, David; Chalmers, James; Capewell, Simon
Abstract : Objective To examine recent trends and social inequalities in age specific coronary heart disease mortality. Design Time trend analysis using joinpoint regression. Setting Scotland, 1986-2006. Participants Men and women aged 35 years and over. Main outcome measures Age adjusted and age, sex, and deprivation specific coronary heart disease mortality. Results Persistent sixfold social differentials in coronary heart disease mortality were seen between the most deprived and the most affluent groups aged 35-44 years. These differentials diminished with increasing age but equalised only above 85 years. Between 1986 and 2006, overall, age adjusted coronary heart disease mortality decreased by 61% in men and by 56% in women. Among middle aged and older adults, mortality continued to decrease fairly steadily throughout the period. However, coronary heart disease mortality levelled from 1994 onwards among young men and women aged 35-44 years. Rates in men and women aged 45-54 showed similar flattening from about 2003. Rates in women aged 55-64 may also now be flattening. The flattening of coronary heart disease mortality in younger men and women was confined to the two most deprived fifths. Conclusions Premature death from coronary heart disease remains a major contributor to social inequalities. Furthermore, the flattening of the decline in mortality for coronary heart disease among younger adults may represent an early warning sign. The observed trends were confined to the most deprived groups. Marked deterioration in medical management of coronary heart disease seems implausible. Unfavourable trends in the major risk factors for coronary heart disease (smoking and poor diet) thus provide the most likely explanation for these inequalities.